Invasive Plants in Natural Areas: Air Potato (Dioscorea bulbifera) - Stephen F. Enloe; Ken Langeland (EDIS)
This publication discusses impacts, distribution, identification, and control of air potato. Written by Stephen F. Enloe and Ken Langeland, and published by the UF/IFAS Agronomy Department, revised December 2021.